Computer networks and internets - Comer, Douglas E. (Prentice Hall, 1997)
Suitable for those with little or no background, this text offers an overview of networking and Internet technology. It provides a tour through all of networking, from the lowest level of data transmission and wiring to the highest levels of application software. An accompanying CD-ROM and Web site provide opportunities for a variety of hands on experiences. The CD contains copies of text figures, digitized images of network wiring and equipment, and files of data that can be used as input to student programs, a key search mechanism, and links to the Web site.